Understanding the status and prospects of biomass industry: processing biowaste into bioenergy pellets - Chia, Wen Yi (2024)
The ever-increasing amount of biowaste has been a global crisis. It urgently requires a sustainable and cost-effective waste management strategy to mitigate the pollution caused by the massive waste. Biowaste can be converted into value-added products through composting, hence significantly reducing the waste volume. Despite the well-known purpose of compost, which is acting as fertiliser and soil enhancer, compost can be used as fuel for energy production. Potential of utilising compost for energy has been tested and studies have proven that the high energy recovery is suitable for implementation in the combustion or incineration plant. However, this field is relatively new that much research is yet to be conducted to provide important findings for commercialisation. To summarise, compost can act as a fertiliser to enhance crop growth, as well as a fuel to generate electricity, making a renewable cycle which is beneficial to the environment. In this thesis, the solid bioenergy or biomass industry is examined, and the utilisation of biowaste for energy generation through aerobic composting technology is explored, with a focus on their potential and associated environmental impacts. The research begins by investigating the production and application of solid bioenergy within the industry, utilising a survey to assess the current production and utilisation of biowaste pellets for renewable energy. Expert opinions from key industry stakeholders across various countries were collected, revealing substantial gaps between industrial players and academic researchers. The study also evaluates market dynamics and challenges in the solid bioenergy sector, providing valuable insights for future research. The survey findings demonstrate end users' openness to innovative approaches in biomass and pellet production, suggesting opportunities for improvement, such as exploring new biomass sources, promoting local resource utilisation, and advancing technology to align with industry demands, ultimately enhancing efficiency and sustainability. Furthermore, the thesis explores the use of an automatic electric composter to rapidly transform biowaste, specifically raw mushroom waste, into solid bioenergy. The study examines fuel properties post-composting and pelletisation, demonstrating a significant increase in calorific value. The process offers an efficient, environmentally friendly, and scalable method for converting biowaste into energy pellets, suitable for industrial applications. Additionally, a life cycle assessment (LCA) study within the thesis assesses the environmental impact of composting biomass pellets for off-grid electrification. The results highlight the environmental advantages of using compost pellets as an alternative to coal-based energy sources. In summary, this research identifies gaps in the solid bioenergy industry and presents an innovative approach to recover energy from biowaste. The findings are valuable for biomass waste generators, particularly those in industrial, commercial, and institutional sectors, aiding them in adopting responsible and sustainable waste management practices.